2003
DOI: 10.1177/01430343030244003
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral School Psychology Internships in NonSchool Settings in the United States

Abstract: School psychologists in the United States work in a variety of settings outside of schools, particularly school psychologists with doctoral degrees. As interns are more likely to obtain employment in a setting similar to the internship site, this study reviewed non-school internship centres that indicated they would consider applications from school psychology doctoral students. Internship directors were asked to complete a questionnaire about the characteristics of the internship site and their perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…These findings are consistent with those of Brown et al. (), who found that internship training directors perceived school psychology applicants as lacking adequate knowledge of psychotherapy and having less experience in individual and group therapy. However, given that these training directors do not accept or review applications from school psychology students, it is unclear how they are able to make this determination.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with those of Brown et al. (), who found that internship training directors perceived school psychology applicants as lacking adequate knowledge of psychotherapy and having less experience in individual and group therapy. However, given that these training directors do not accept or review applications from school psychology students, it is unclear how they are able to make this determination.…”
Section: Discussionsupporting
confidence: 92%
“…A 15‐ to 20‐minute survey was developed by the researchers in the present study to gain information about why some training directors of APA‐accredited programs that include one or more major rotations with children and/or adolescents choose to allow or prohibit school psychology doctoral students from applying for their internship program. Survey items were developed based on previous literature (i.e., Brown et al., ; Gayer et al., ) and aspects of the APPIC Application for Psychology Internship (AAPI) that are reviewed when considering applicants (Ginkel, Davis, & Michael, ). The survey included 38 questions that yielded information on 82 variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When those training directors who did not permit school psychology students to apply for their internship programs were asked why such students were not permitted to apply, they generally reported that they perceived school psychology applicants as having less relevant practicum experiences in fewer settings and as having narrower training, with less knowledge of psychopathology and less non‐school intervention experience. These findings were generally consistent with those of Brown, Kissell, and Bolen (), who found that school psychology students were perceived by 34% of internship training directors as having less practicum experience in non‐school settings and having less experience providing individual, group, and family therapy services.…”
Section: Training Director Perceptionssupporting
confidence: 89%
“…Without a doubt, there is considerable support for the anecdotal reports from SP students about the limited choices of internship sites available to them through the APPIC Match, along with the experience of being “locked out” of many sites. Some previous research also supports this perspective (e.g., Brown, Kissell, & Bolen, ; Gayer, Brown, Gridley, & Treloar, ). It is reasonable to assume that many internship Training Directors perceive SP students as lacking in the skills, background, or experiences that are relevant to their internship sites and thus deem them as unqualified for their programs.…”
Section: Implications and Recommendationsmentioning
confidence: 64%